2019
DOI: 10.4236/ce.2019.102034
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Writing: An Integration of Snack Bars and Hi-Five Fingers via Social Media

Abstract: English has been the second language taught in schools in Malaysia both in primary and secondary level. Writing skill has been a major part of the English education in the Malaysian schools. However, writing skill is the most difficult skill to master by our Malaysian pupils. Both teachers and pupils find teaching and learning of writing a difficult task to accomplish in the classroom. This can be caused by the lack of teacher-pupil time in school. Teachers do not have time to give feedback to pupils after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…It helps pupils to develop their confidence level by uploading status, voicing out opinions and writing in English on social media. Pupils are more into writing and show their interests when they write their essays out of the normality (Chandran et al, 2019). Writing rules on social media platforms are informal, thus it is undemanding for users who are not consummate in the English language to deliver their thoughts and ideas (Vikneswaran & Krish, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It helps pupils to develop their confidence level by uploading status, voicing out opinions and writing in English on social media. Pupils are more into writing and show their interests when they write their essays out of the normality (Chandran et al, 2019). Writing rules on social media platforms are informal, thus it is undemanding for users who are not consummate in the English language to deliver their thoughts and ideas (Vikneswaran & Krish, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They also learn lots of new things instead of learning only vocabulary and grammatical rules, and online writing is a new method that needs to be implemented to enhance their English writing skills. Amongst all skills in learning the English language, writing skills are the most strenuous skill to achieve by Malaysian pupils where teachers and pupils agreed that to accomplish the teaching and learning of writing is demanding (Chandran et al, 2019). Pupils in the new generation are having problems in writing formally.…”
Section: Introductionmentioning
confidence: 99%
“…While providing young people with both interesting and encouraging tools, social media can create fun and interactive content and allow young people to reach effective and comfortable learning process (Imlavi & Gregg, 2014¸Kawachi, 2019. Social media's supporting collaborative learning and critical thinking, by allowing their members to work in personalized environments, can be a way to improve its members' skills such as communication and writing (Dizon, 2016;Suswati & Saleh, 2019;Chandran, Plaindaren, Pavadai & Yunus, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the studies revealed that the pupils' grades are increasing after the implementation of high-five fingers and snack-bars, which is SNSs is part of the learning and teaching platform (Chandran, Plaindaren, Pavadai, & Yunus, 2019).…”
Section: Snss and English Writing Skillsmentioning
confidence: 99%